2006
DOI: 10.1158/0008-5472.can-06-0399
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Antigen-Specific Vaccination and Toll-Like Receptor Stimulation against Established Transplanted and Autochthonous Melanoma in Mice

Abstract: Malignant melanoma is an attractive model disease for the development of antigen-specific immunotherapy because many antigens recognized by tumor-specific T cells have been identified. In C57BL/6 mice, genetic immunization with recombinant adenovirus encoding xenogeneic human tyrosinase-related protein 2 (Ad-hTRP2) induces protective but not therapeutic cellular immunity against growth of transplanted B16 melanoma cells. Here, we additionally applied CpG DNA and synthetic double-stranded RNA, which activate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 33 publications
(41 reference statements)
1
22
0
Order By: Relevance
“…39 have shown that combined immunotherapy with vaccination and adjuvant injection delays melanoma growth, in concordance with our data. By further adding cyclophosphamide and adoptive transfer of tumor-specific T lymphocytes into these regimens, Kohlmeyer et al 40 have shown that a combination chemoimmunotherapy results in complete regression of both primary and metastatic melanoma in the Hgf-Cdk4 R24C melanoma mouse model.…”
Section: Discussionsupporting
confidence: 92%
“…39 have shown that combined immunotherapy with vaccination and adjuvant injection delays melanoma growth, in concordance with our data. By further adding cyclophosphamide and adoptive transfer of tumor-specific T lymphocytes into these regimens, Kohlmeyer et al 40 have shown that a combination chemoimmunotherapy results in complete regression of both primary and metastatic melanoma in the Hgf-Cdk4 R24C melanoma mouse model.…”
Section: Discussionsupporting
confidence: 92%
“…CD4 + T-cell help is essential for the differentiation and expansion of CTLs [35], as well as their maturation into functional memory CTLs [36]. To achieve CD4 + T-cell help, a universal T helper epitope, PADRE was used in VM [37].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, studies have reported both beneficial and detrimental effects following treatment with TLR agonists. For instance, Hirabayashi et al, [6] reported that Poly(I:C), a TLR3 agonist, could slow the growth of a panel of tumors including the commonly used breast cancer cell lines MCF7, T47D, MDA-MB-468, MDA-MB-453 and SKBR3, whereas a panel of normal cell lines were unaffected, and Tormo et al, [7] reported that Poly(I:C) and CpG ODN in combination with an adenoviral vector encoding tyrosinase-related protein 2 (TRP2) could delay growth of the B16 melanoma. On the other hand, Huang et al, [8] reported that the MC26 murine colon carcinoma responded to LPS in a manner that inhibited anti-tumor immunity.…”
Section: Introductionmentioning
confidence: 99%